C30‐45 long‐chain alkyls modified silsesquioxane: A promising additive for polyethylene. Issue 5 (12th February 2021) - Zhang, Yi; Zhang, Yongjie; Yu, Fan; Yang, Wei; Li, Xiaopei; Wang, Zhichao; Wang, Shuai
Abstract: A novel commercial available and inexpensive long‐chain alkyl (C30‐45) modified silsesquioxane, namely (C30‐45 alkyl)dimethylsilyl polypropylsilsesquioxane (C30PSS), was applied as a functional filler for linear low density polyethylene (LLDPE). For comparison, LLDPE/octaisobutyl polyhedral oligomeric silsesquioxane (BuPOSS) nanocomposites were also prepared via melt blending. The chemical and crystalline structures of C30PSS and BuPOSS were first identified by Fourier transform infrared spectroscopy, solid 29 Si NMR, and X‐ray diffraction. The dispersion of two fillers in the polymer matrix was analyzed via scanning electron microscopy and X‐ray energy dispersive spectroscopy. The rheological, tensile, and thermal properties of pristine LLDPE, LLDPE/C30PSS, and LLDPE/BuPOSS composites were systematically studied. Our results showed that C30PSS can serve as a promising and low‐priced filler for LLDPE with respect to its fine dispersion in LLDPE and its abilities to improve the rheological and mechanical properties of LLDPE. Abstract :